2020
DOI: 10.1186/s12964-020-00564-3
|View full text |Cite
|
Sign up to set email alerts
|

The TNF/TNFR2 signaling pathway is a key regulatory factor in endothelial progenitor cell immunosuppressive effect

Abstract: Background Endothelial progenitor cells (EPCs) are non-differentiated endothelial cells (ECs) present in blood circulation that are involved in neo-vascularization and correction of damaged endothelial sites. Since EPCs from patients with vascular disorders are impaired and inefficient, allogenic sources from adult or cord blood are considered as good alternatives. However, due to the reaction of immune system against allogenic cells which usually lead to their elimination, we focused on the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 56 publications
5
80
0
Order By: Relevance
“…We have recently demonstrated that EPCs bear immunosuppressive effect, secrete anti-in ammatory cytokines and are tolerated for certain days after their administration in xenogeneic ischemia model. 30,31 However, our experience demonstrates that compared to other immunosuppressive cells like Tregs and MSCs, EPCs are signi cantly less suppressive. This could potentially affect the success of cell therapy outcome.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…We have recently demonstrated that EPCs bear immunosuppressive effect, secrete anti-in ammatory cytokines and are tolerated for certain days after their administration in xenogeneic ischemia model. 30,31 However, our experience demonstrates that compared to other immunosuppressive cells like Tregs and MSCs, EPCs are signi cantly less suppressive. This could potentially affect the success of cell therapy outcome.…”
Section: Discussionmentioning
confidence: 87%
“…Compared to APB-EPCs, CB-EPCs are more clonogenic, e cient and immunotolerated. 19,20,30 Nevertheless, the choice of allogenic sources usually raise the concern of immune rejection risking the achievement of the desired bene t.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although FL-MSCs gave rise to more iT regs than BM-MSCs, both were able to induce Foxp3 expression. To better de ne iT regs induced in the presence of FL and BM-MSC, we characterized them and compared their activation/suppressive pro le by FACS using different activation/suppressive markers, such as CTLA4, GITR and ICOS, [83][84][85] . We focused our analysis on commonly accepted CD4 + Foxp3 + iT regs.…”
Section: Fl-mscs Induced It Regs Display a More Active Phenotype Thanmentioning
confidence: 99%